The Composition of Haemoglobin A2 In Haemoglobin EHaemoglobinopathy by Capillary Electrophoresis (The Planet, 2024)
Introduction: Hemoglobin E (HbE) hemoglobinopathy is one of the most prevalent inherited hemoglobin disorders in Southeast Asia, including Bangladesh. Elevated hemoglobin A2 (HbA2) levels serve as an important diagnostic marker for distinguishing HbE-related conditions. This study aimed to analyze the composition of HbA2 in individuals with HbE hemoglobinopathy using capillary electrophoresis. Methods & Materials: A cross-sectional study was conducted on 50 participants clinically diagnosed with HbE hemoglobinopathy. Hemoglobin analysis was performed using the Sebia Capillarys 2 system. Data on HbA2 levels, anemia severity, and hemoglobinopathy subtypes were analyzed, and statistical significance was determined at p
Keywords: Hemoglobin E; Hemoglobin A2; Capillary Electrophoresis; Hemoglobinopathy; Anemia; Diagnostic Tools; Bangladesh